The evolution of climate change guidance for fluvial flood risk management in England. (April 2017) - Reynard, Nicholas S; Kay, Alison L; Anderson, Molly; Donovan, Bill; Duckworth, Caroline
Floods are one of the biggest natural hazards to society, and there is increasing concern about the potential impacts of climate change on flood occurrence and magnitude. Furthermore, flood risk is likely to increase in the future not just through increased flood occurrence, but also through socio-economic changes, such as increasing population. The extent to which adaptation measures can offset this increased risk will depend on the level of future climate change, but there exists an urgent need for information on the potential impacts of climate change on floods, so that these can be accounted for by flood management authorities and local planners aiming to reduce flood risk. Agencies across the UK have been pro-active in providing such guidance for many years and in refining it as the science of climate change and hydrological impacts has developed. The history of this guidance for fluvial flood risk in England is presented and discussed here, including the recent adoption of a regional risk-based approach. Such an approach could be developed and applied to flood risk management in other countries, and to other sectors affected by climate change.